Unforgettable [large type] - Perry, Trish, 1954- (Center Point Pub., 2011)
"Rachel Stanhope tries to see the good in everyone. But Josh Reegan tests even her good graces when they meet outside her Arlington, Virginia, dance studio in 1951. He's attractive, yet his cynicism and cockiness are hard to tolerate. A journalist and former World War II Air Force pilot, Josh considers ballroom dancing a frivolous waste of time. Although Rachel's confident nature is a refreshing challenge, he wouldn't tangle with her if his newspaper hadn't assigned him to cover her studio's competition in New York City. Between the melodrama of ballroom antics and the real drama of political corruption, Rachel and Josh have their hands full. The last thing either of them expects is mutual need and support. But once they stop dancing around the truth, the results are unforgettable" -- Cover verso.